Farm production diversity: is it important for dietary diversity? Panel data evidence from Uganda - Sekabira, H.; Nalunga, S. (MDPI, 2020)
The substantial existence of malnutrition globally, especially in developing countries, has usually driven policy initiatives to focus on improving household food security and nutrition primarily through prioritizing farm production diversity. Although indeed some empirical evidence has pointed to farm production diversity remedying malnutrition, other evidence has pointed to markets. Therefore, evidence is mixed and may be country or region variant. To contribute to closing such a gap in the literature, we used three waves of national panel survey data from Uganda and panel regression models to investigate associations between farm production diversity and dietary diversity, as well as impact pathways. We found that farm production diversity was positively and significantly associated with household dietary diversity. Farm production diversity influenced dietary diversity through own farm production, and market consumption food security pathways. The own farm production pathway showed a stronger associated impact. Increasing food expenditure by 1000 UGX via own farm production yielded an eight percentage point increment in household dietary diversity, while an equal expenditure via markets yielded a 5.3 percentage point increment. We also found existence of gender effects. Male headed households were associated with relatively poorer household dietary diversity. These findings could have broader implications for countries practicing smallholder agriculture.